Vascular Cells Proteome Associated with Bradykinin and Leptin Inflammation and Oxidative Stress Signals - Moustafa Al Hariri; Miran A. Jaffa; Richard Saoud; Jingfu Zhao; Rui Zhu; Aneese A. Jaffa; Ghewa A. El-Achkar; Mayssam Moussa; Firas Kobeissy; Anwarul Hassan; Fuad N. Ziyadeh; Yehia Mechref; et al. (MDPI AG, 2020)
Among the primary contributors to cardiovascular diseases are inflammation and oxidative imbalance within the vessel walls as well as the fibrosis of rat aortic smooth muscle cell (RASMC). Bradykinin (BK) and leptin are inflammatory modulators that are linked to vascular injury. In this study, we employed tandem LC-MS/MS to identify protein signatures that encompass protein abundance in RASMC treated with BK or leptin followed by systems biology analyses to gain insight into the biological pathways and processes linked to vascular remodeling. In the study, 1837 proteins were identified in control untreated RASMC. BK altered the expression of 72 (4%) and 120 (6.5%) proteins, whereas leptin altered the expression of 189 (10.2%) and 127 (6.5%) proteins after 24 and 48 h, respectively, compared to control RASMC. BK increased the protein abundance of leptin receptor, transforming growth factor-β. On the other hand, leptin increased the protein abundance of plasminogen activator inhibitor 1 but decreased the protein abundance of cofilin. BK and leptin induced the expression of inflammatory cytokines such as tumor necrosis factor alpha (TNF-α) and interleukin-1β (IL-1β) and pathway analysis revealed the activation of mitogen-activated protein kinases (MAPKs) and AKT pathways. The proteome profile in response to BK and leptin revealed mechanistic interplay of multiple processes that modulate inflammation and oxidative stress signals in the vasculature.